Laboratory and clinical findings in hospitalized pregnant women with Covid-19 based on disease outcome during the outbreak of Delta variant in Ardabil (summer and autumn 2021) - Shahla Farzipour; Faranak Shojaei; Shahram Habibzadeh; Mohammad Reza Aslani; Samira Shahbazzadegan (Mashhad University of Medical Sciences, 2022)
Introduction: Due to the high risk of Covid-19 disease, especially delta variant in pregnant women, as well as the novelty of this epidemic in the world and the lack of similar studies in Iran and the region, it seems necessary to perform a study on mortality rate and laboratory and clinical findings of the disease in pregnant women. Therefore, this study was performed aimed to determine the laboratory and clinical findings in hospitalized pregnant women with Covid -19 based on disease outcome during the outbreak of Delta variant (summer and autumn 2021) in Ardabil province. Methods: In this cross-sectional and descriptive study, all pregnant women with Covid-19 admitted to the hospitals of Ardabil province in summer and autumn 2021 at the time of delta outbreak were included. Finally, 187 infected pregnant mothers were studied. Demographic information, clinical signs and laboratory findings were studied in all mothers. Data were analyzed by SPSS (version 24) and Fisher Exact test and Pearson Correlation. P<0.05 was considered statistically significant. Results: Of the 187 infected pregnant women, 8 mothers died. Comorbidity was observed in 41 pregnant women. The most common clinical finding was shortness of breath (Dyspnea) and cough, and the most common laboratory finding was lymphopenia. Comparing the cured and dead mothers according to laboratory findings using Fisher's exact test showed that the difference between ALT (p <0.05), lactate dehydrogenase (p <0.001), AST (p <0.001), BS (P <0.05), creatinine (p <0.05) and total bilirubin (p<0.05) were statistically significant between the two groups. Conclusion: Infection to delta variant of Covid-19 disease resulted in 187 hospitalizations and 8 deaths of pregnant mothers in Ardabil province. Shortness of breath (Dyspnea) and cough were the most common clinical findings and lymphopenia was the most common laboratory finding.